Technological adaptation of the MBKM Kampus Mengajar VII Program for Teknologi Pendidikan FIP UNM students - P. Pattaufi; I Made Tegeh; Farida Febriati (Inovasi Kurikulum)
The Merdeka Belajar Kampus Merdeka (MBKM) Program is integral to higher education in Indonesia. This program provides opportunities for students to gain practical experience in the field. This study explores the technology adaptation process of Teknologi Pendidikan students at FIP UNM in the MBKM Kampus Mengajar VII Program. In addition, this study also identifies the challenges faced by students and the strategies used to overcome them. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations during field activities, and analysis of related documents. The data obtained are explained through the reduction, presentation, and interpretation stages. The analysis focused on key themes, such as technology adaptation strategies, challenges faced by students, and the implementation of the MBKM program in the future. This study is expected to provide a more comprehensive insight into the technology adaptation process of Educational Technology students at FIP UNM during the MBKM Kampus Mengajar VII Program. These findings will provide valuable contributions to higher education institutions in improving technology integration in field programs and guiding students and teachers in facing the challenges of technology adaptation.